A compreensão dos gêneros textuais evocada pelas capacidades de linguagem em propostas de atividades nos livros didáticos do 6º ano do ensino fundamental - Sousa, Maria Greiciane Mesquita (2021)
The textbook is the main element that assists the teacher in his planning, in the execution of classes and as a guide for the fulfillment of the school curriculum. Through the PNLD, this important material is the main didactic resource for the learning of public school students in Brazil has been improved to keep up with changes in education. Regarding language teaching, the textbook is one of the teaching resources that provides a deeper understanding of language actions through textual genres, reflecting on the critical-reflective, social and cultural formation of the student. With regard to language teaching, one of the theoretical bases adopted in the official documents, like the National Curriculum Parameters , the Common National Curriculum Base, and in Ceará the Reference Curriculum Document of Ceará, it is sociodiscursive interactionism that understands language as an instrument of interaction. In the scope of ISD, from the didactics of genres, the Geneva School conducts its studies on language actions highlighting the language skills of highlighting language capabilities with components necessary for understanding textual genres. In view of this panorama, we propose to analyze how the exercises of understanding textual genres of the 6th grade textbooks of elementary school - Final Years Require Students' Language Skills. The research was developed in the field of applied linguistics, anchored in the theoretical assumptions of Sociodiscursive Interactionism, elaborated by Bronckart (1999), and the didactics of textual genres for the teaching of languages, elaborated by Dolz, Pasquier, Bronckart (1993) and Dolz, Schneuwly (2004), understanding the importance of studies that develop for the teaching of genres, the performance of the language teacher and the teaching materials used as teaching tools, considering the directions exposed in the PCN, BNCC and DCRC. We analyze the statements of the exercises of understanding textual genres who composed two 6th grade Portuguese-language books; the book Portuguese Languages, approved by the PNLD for the triennium 2017/2018/2019 and the book Connects in the language, approved by the PNLD for the triennium 2020/2021/2022. Both used in public schools in the city of Fortaleza - CE. The research data show us that the analyzed textbooks present an interactionist perspective of language and that there is a concern with the teaching of genres that are in the students' daily lives. However, in relation to the statements of the exercises analyzed in the book Portuguese Languages, we noticed that there is a tendency to work on the global view of the text, with a predominance of statements that require the use of action skills, since most of the statements make the students search for explicit information in the text. On the other hand, in the book Watch out for the Language, we noticed that the statements of the exercises require students to use action skills, discursive skills, and linguistic-discursive skills.